Calculating economic weights for sheep sire breeds used in different breeding systems - Wolfová, M; Wolf, J; Milerski, M (Journal of animal science, 2011)
The objective of this paper was to adapt gene-flow methodology for the calculation of economic weights (EW) for direct and maternal traits and trait components in sheep and to apply this methodology to the Suffolk breed in the Czech Republic. Computer programs were developed in which annual-lambing sheep production systems with purebreeding or partial terminal crossing were simulated. Using these programs, the EW for 12 production and functional traits were estimated for i) Suffolk sires whose sons were used both in purebreeding and in terminal crossing with the 4 dual-purpose breeds, Romanov, Sumavska, Romney, and Merinolandschaf; and ii) Suffolk sires used only for terminal crossing. For case (i), the EW were at first calculated separately for the purebreeding system and for the crossing systems with the 4 dual-purpose breeds in dam position. Compound EW for the general breeding goal for Suffolk were then estimated as weighted averages from the EW in the 5 subsystems. Standardized EW were calculated by multiplying the marginal EW with the genetic SD of the trait, and relative EW were defined as absolute values of the standardized EW expressed as percentage of the sum of the absolute values of the standardized EW over all traits. The 5 most important trait components for Suffolk sires whose sons were used both in purebreeding and in terminal crossing were (relative EW given in parentheses): the direct components of survival rate until weaning (21.0%), daily BW gain until weaning (14.1%), survival rate at birth (14.0%), the maternal component of survival rate until weaning (10.7%), and litter size at lambing (7.6%). There were only small differences between the relative EW calculated for the whole system with pure- and crossbreeding and the relative EW for the purebred system within the Suffolk breed. Therefore, selection of Suffolk rams using a selection index based on the compound EW is expected to be of high efficiency in all of the simulated breeding systems. Only direct traits were relevant for Suffolk sires used only for terminal crossing; the most important (range of relative EW calculated for the 4 crossing systems given in parentheses) were survival rate until weaning (35.2 to 36.5%), daily BW gain until weaning (24.2 to 26.3%), and survival rate at birth (23.7 to 24.8%).
Keywords: tok genů; Animals; biologické modely; rozmnožování; Female; Gene Flow; hmotnostní přírůstek; vlna; ženské pohlaví; zemědělství; Weight Gain; Reproduction; ovce; Models, Biological; Genetic Variation; Agriculture; Wool; Male; Sheep; zvířata; mužské pohlaví; chov; genetická variace; Breeding